غزواتِ نبویہ ﷺ میں اہلِ کتاب کے ساتھ اخلاقِ حسنہ کے مظاہر: Manifestations of Akhlaq-e-Hasanah (good manners) with the People of the Book (Ehl-e-Kitab) in Ghazwat-e-Nabawiyyah ﷺ - Adnan, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2023)
When we study about the life of Holy Prophet (ﷺ), his life demand from Muslims to protect the dignity and honour of their Muslim brothers. They not only protect or care the right of their Muslim brothers in their life but also protect their dignity after their death. In the light of Holy Prophet Life the circle of human rights is so vast. In this, his life teaches us the turidicul, rights, marriage, settlement different between good or evil, isonomy and the verses of martyr and the noble behaviour with Jews and Christians. There is a big role of ethics on the human personality. The ethics is the tester of good or bad person Human with the noble ethics the Muslims. To be remembered as staying up all the night and to fast. The ethics play important role in the life of Human. In the life of Prophet (ﷺ) we know about his good deeds and noble behavior with non Muslims. The success of the Holy Prophet preaching is only because of his ethics and truthness. Islam Universal Religion. It’s Teachings and pregnative system is the everlasting. In this modern period there is no way except Islam to get Rid the unsolved problems of the age. The beloved Prophet (ﷺ) “Sira Mubarak” the way of light only. There is aspect of the life without the real pregnative system. Peace and the War both are in the teaching of the Holy Prophet (ﷺ). Peace, progress contentment, satisfaction, true, unity, brotherhood in the lightment of the “Uswa Hasna”. Let’s seek the real way in our beloved Prophet (ﷺ). Key Words: Holy Prophet, Ghazwa, Akhlaq-e-Hasanah, Ehl-e-Kitab, War, Ethics.